Study On The Characteristics And Adsorption Behavior Of Natural Rubber – Halloysite Nanotubes Films Towards Methylene Blue - Tan, Yee Chien (2019)
Natural rubber – halloysite nanotubes (NR-HNT) films were prepared by incorporating different weight percentages (10 – 70 wt%) of halloysite nanotubes (HNT) into natural rubber (NR) and were used to adsorb methylene blue (MB). The samples were characterized using attenuated total reflectance fourier transform infrared spectroscopy (ATR-FTIR), x-ray diffraction (XRD), scanning electron microscopy (SEM), thermogravimetric analysis (TGA) and point of zero charge (pzc). It was found that at lower wt%, the HNT was well-dispersed. When the wt% of HNT was increased, it made it harder to be dispersed and caused aggregation of the HNT, which affected the thermal properties of the NR. MB adsorption studies were carried out to investigate the ability of the samples to adsorb dye. Different parameters such as the wt% of HNT, initial concentration of MB, pH, adsorbent dosage and temperature were studied to determine the optimum conditions for the adsorption of MB by the NR-HNT films. The results showed that one film of 10 wt% NR-HNT (approximately 2.3 x 2.6 cm) has the best ability to adsorb dye in aqueous solution with the initial concentration of MB = 16 mg L-1 at pH 9.7 and at 39 ˚C. The adsorption kinetics and isotherms were also investigated to further understand these results. It was found that the experimental data are successfully fitted into type 1 pseudo second-order kinetic model. The NR and 50 wt% NR-HNT best fit Temkin isotherm while the 10 wt% NR-HNT fits Langmuir isotherm.